Концепція законопроекту та її значення для підвищення якості законів - Червінська, Наталія Володимирівна; Червинская, Наталья Владимировна; Chervinskaja, Natal'ja (Одеса : Юрид. л-ра, 2014)
This article analyzes the category “the concept of the bill”, which is scientific and practical interest for legislative activity in Ukraine, the essence and meaning of the concept of the bill to improve the quality of laws. It was concluded that to improve the quality of laws the most effective approach is undoubtedly in recognition that the scientific concept of development is a fundamental prerequisite for the preparation of laws. In this regard, the proposed systematic list of elements of the concept of the bill and proved obligatoriness training concept of the law. An attempt to provide suggestions for improving training concepts as law during the legislative process.
Червінська Н. В. Концепція законопроекту та її значення для підвищення якості законів / Н. В. Червінська // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 55-61.
Keywords: концепція; концепція законопроекту; якість законів; законотворчий процес; концепция; концепция законопроекта; качество законов; законотворческий процесс; concept; concept of law; quality of laws; legislative process